Rapidly growing mycobacteria as emerging pathogens in bloodstream and device-related infection: a case of pacemaker infection with Mycobacterium neoaurum. Issue 3 (June 2015) - Hayton, Emma-Jo R.; Koch, Oliver; Scarborough, Matthew; Sabharwal, Nikant; Drobniewski, Francis; Bowler, Ian C. J. W.
Abstract : Introduction: We present a case of pacemaker infection with a rapidly growing mycobacterium (RGM). Case presentation: An 80-year-old woman presented with fever, weight loss and malaise for 2 months. Mycobacterium neoaurum was isolated from blood cultures and from cardiac pacing wires. She made an excellent recovery with combination antimicrobial therapy and removal of the device. Conclusion: Such RGMs are encountered with increasing frequency in intravascular device-associated infections, posing challenges for both laboratory identification and clinical management.